2014
DOI: 10.1016/s2007-5057(14)70937-8
|View full text |Cite
|
Sign up to set email alerts
|

Herramientas de estudio utilizadas por alumnos de ciencias de la salud en la materia de Anatomía

Abstract: Introducción: Las herramientas de estudio varían de acuerdo al acceso a la tecnología y presupuesto de la Facultad, en Anatomía el uso de modelos virtuales y videos en línea, son una realidad con cada vez mayor uso. Objetivo: Conocer las herramientas de estudio más utilizadas por alumnos que cursaron la materia de Anatomía General en cuanto a tiempo de estudio, tecnología de la información que utilizan, libros preferidos, uso de modelos anatómicos y utilidad de las disecciones. Método: Se realizó u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Using cadavers to teach Anatomy has been regular practice from centuries and has proved to continue being an cornerstone instead of the most modern technological resources (Biasutto et al, 2006;Azer and Eizenberg, 2007;Cahill and Ettarh, 2008;Sugand et al, 2010;Dereje, 2014;Narvaez-Hernandez and Murillo-Rabago, 2014;Arráez-Aybar et al, 2014). However, unclaimed bodies as source of cadaveric material is not acceptable anymore, based on human rights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using cadavers to teach Anatomy has been regular practice from centuries and has proved to continue being an cornerstone instead of the most modern technological resources (Biasutto et al, 2006;Azer and Eizenberg, 2007;Cahill and Ettarh, 2008;Sugand et al, 2010;Dereje, 2014;Narvaez-Hernandez and Murillo-Rabago, 2014;Arráez-Aybar et al, 2014). However, unclaimed bodies as source of cadaveric material is not acceptable anymore, based on human rights.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, all dissected bodies are obtained by donation, but the number has reduced to critical levels. Digital and interactive resources have demonstrated not being able to replace the corpses, although are recognized as very useful complementary options (Biasutto et al, 2006;Azer and Eizenberg, 2007;Cahill and Ettarh, 2008;Sugand et al, 2010;Dereje, 2014;Narvaez-Hernandez and Murillo-Rabago, 2014;Arráez-Aybar et al, 2014). Then, the need of a donation program cannot be delayed for longer.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Antomy is recognized as basic and essential for medical training since ancient times and the human body is its corner stone. Corpses are an invaluable resource for teaching and research in Anatomy and have demonstrated to be irreplaceable for graduate and postgraduate student's training (Biasutto et al, 2006;Azer and Eizenberg, 2007;Cahill and Ettarh, 2008;Sugand et al, 2010;Cornwall et al, 2012;Dereje, 2014;Narvaez-Hernandez and Murillo-Rabago, 2014;Arráez-Aybar et al, 2014). Cadaver donation provides 100% of the total corpses used for university teaching in Anatomy in Australia, Austria, Canada, Chile, Czech Republic, Denmark, France, German, Ireland, Japan, Malta, Netherlands, New Zealand, Poland, South Korea, Spain, Sri Lanka, Sweden, Switzerland, Thailand and United Kingdom, and most of the bodies in China, Portugal, South Africa, Taiwan, United States and Uruguay among the participating countries in the study of Habicht et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…A fines del siglo XX e inicios del XXI se difundió la idea de que los advances tecnológicos podrían reemplazar el uso del material cadavérico. Aunque los recursos digitales para la enseñanza han aportado y facilitado el estudio, no han podido reemplazar a los cuerpos humanos en su posibilidad de identificar texturas, elasticidad, tridimensionalidad, relaciones, variaciones anatómicas, etc., habiendo sido reconocidos como irremplazables en la actualidad (Biasutto et al, 2006;Azer and Eizenberg, 2007;Cahill and Ettarh, 2008;Sugand et al, 2010;Dereje, 2014;Narvaez-Hernandez and Murillo-Rabago, 2014;Arráez-Aybar et al, 2014). La pandemia por COVID-19, que se iniciara en China a fines de 2019 y continua aún en 2021, ha impuesto un nuevo desafío para el mundo, en el que las Ciencias de la Salud se ven muy comprometidas tanto en la práctica professional, la investigación y la formación de recursos humanos.…”
Section: Introductionunclassified